Kepatuhan membayar zakat: analisis kutipan dan ketirisan zakat fitrah di Selangor - Mohd Hussin Mohd Yahya, Muhammad Fidlizan, Roshidi Ahmad Mohamad Ali, (N/A, 2013)
Kepatuhan membayar zakat: analisis kutipan dan ketirisan zakat fitrah di Selangor by Mohd Hussin Mohd Yahya, Muhammad Fidlizan, Roshidi Ahmad Mohamad Ali,